2012
DOI: 10.5966/sctm.2011-0028
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic Stem Cell-Based Cardiopatches Improve Cardiac Function in Infarcted Rats

Abstract: Pluripotent stem cell-seeded cardiopatches hold promise for in situ regeneration of infarcted hearts. Here, we describe a novel cardiopatch based on bone morphogenetic protein 2-primed cardiaccommitted mouse embryonic stem cells, embedded into biodegradable fibrin matrices and engrafted onto infarcted rat hearts. For in vivo tracking of the engrafted cardiac-committed cells, superparamagnetic iron oxide nanoparticles were magnetofected into the cells, thus enabling detection and functional evaluation by high-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 70 publications
(90 reference statements)
2
23
1
Order By: Relevance
“…Although some studies have utilized strain imaging from both tagged MRI and cardiac ultrasound to assess therapeutic efficacy, 2931 its detection limits and limits of agreement for these localized regenerative therapies have not been evaluated. To fill this gap, we validated strain analysis by using 3D tagged MRI and 2D ultrasound imaging data from infarcted rat hearts before and after EHM transplantations or sham surgery (control).…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies have utilized strain imaging from both tagged MRI and cardiac ultrasound to assess therapeutic efficacy, 2931 its detection limits and limits of agreement for these localized regenerative therapies have not been evaluated. To fill this gap, we validated strain analysis by using 3D tagged MRI and 2D ultrasound imaging data from infarcted rat hearts before and after EHM transplantations or sham surgery (control).…”
Section: Discussionmentioning
confidence: 99%
“…The approach described in this protocol is limited to optical tracking and, although the possibility of using infrared excitation leads to increased penetration depth with respect to fluorescence based techniques; optical imaging cannot be extended to whole body and therefore should be complemented by magnetic detection 21 . Previous published work showed several approaches to assess structure and movement of cardiac cell clusters, including labeling by fluorescent dyes 22 , quantum dots 23,24 , super-paramagnetic iron oxide nanoparticles 25 , and up-conversion fluorescent particles [26][27][28] . The advantages of HNPs with respect to these nanoprobes are associated with absence of bleaching over extended periods of time, increased imaging penetration, wavelength tunability for increased contrast with respect to autofluorescence.…”
Section: Movie 1 Discussionmentioning
confidence: 99%
“…PEGylated 15 nm gold nanoparticles grafted within the poly(methylglutarimide) (PMGI) nanofibers along with adhesion peptides RGD and HBP (heparin binding protein) induced the differentiation of pluripotent stem cells to cardiomyocytes . Superparamagnetic iron oxide (SPIO) nanoparticles, when transfected within the ESC pretreated into the cardiac induction medium . These cells were loaded in a fibrin matrigel and injected to ischemic scar tissue of rat AMI model.…”
Section: Nanocompositesmentioning
confidence: 99%
“…These cells were loaded in a fibrin matrigel and injected to ischemic scar tissue of rat AMI model. High‐resolution MRI studies revealed heart function after six weeks due to ESC commitment to cardiac lineage in fibrin matrix . Martinelli et al showed neonatal cardiomyocytes interact with multiwalled carbon nanotubes (MWCNT) forming desmosome mediated tight junctions, which helps in the rapid proliferation and differentiation to mature cardiomyocyte.…”
Section: Nanocompositesmentioning
confidence: 99%